Coaxing corporations: Enriching the conceptualization of governments as strategic actors - Gill, Michael J.; Gill, David J. (Strategic Management Journal, 2024)
Abstract Research Summary Little is known about how governments secure discrete resources from global corporations over which they have limited direct control. Utilizing declassified archival sources, we examine how the UK government influenced Moody's and Standard & Poor's to provide the highest possible credit ratings in 1978, despite the UK receiving an International Monetary Fund bailout 2 years earlier. We develop a process model to explain how democratic government officials employ distinctive processes to enable and facilitate a nonmarket approach of corporate coaxing to influence corporations' decision making. We thereby enrich the concept of governments as a strategic actors by illuminating how officials act to secure resources when in a position of dependence. Managerial Summary We sought to understand how governments attempt to influence corporations' decision making when they have limited direct control over these corporations. We examined the historical case of the UK government seeking to influence Moody's and Standard and Poor's. In this case, we identified the distinctive strategy of corporate coaxing to explain how government officials navigate the distinctive constraints, and leverage the unique strengths, of their democratic state, to exert influence on private and global corporations. Our findings show how governments can be more active stakeholders in corporate activity than commonly assumed, as their subtle influence can extend beyond state policies or regulations.